Implementation Of The Dhuha Prayer Habit Method In Developing Positive Character In Children Aged 5-6 Years At Cahaya Asta Paud In The 2024/2025 Academic Year - Astuti, Maria; Alawiyah, Tuti; Marzoan, Lalu (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Abstract. This study aims to describe the Implementation of the Dhuha Prayer Habituation Method in Developing Positive Character of 5-6 Year Old Children at PAUD Cahaya Asta Dusun Orong Ramput Medana Village, Tanjung District, North Lombok Regency. This research was conducted at PAUD Cahaya Asta Medana Village in Group B2 Semester 2 of the 2024/2025 school year with 10 students. The focus of this research is on the process of habituation of dhuha prayer, supporting and inhibiting factors for habituation of dhuha prayer. This study uses a qualitative approach with a descriptive method in the type of field research. Based on the results of the study that in the process of habituation of dhuha prayer there are stages carried out by the teacher, namely the preparation, implementation and evaluation stages. The preparation stage includes the preparation of lesson plans, the provision of tools and media, and the habituation of discipline such as lining up and ablution, while the implementation stage of the dhuha prayer is carried out in congregation with the guidance of the teacher, involving memorization of readings, prayer movements, as well as dhikr and prayer activities together. Evaluation is done through direct observation, personal approach, and collaboration with parents to assess children's positive character development, such as discipline, independence, and spiritual abilities. As for the supporting and inhibiting factors in implementing Dhuha prayer habituation at PAUD Cahaya Asta, the main supporting factors include the support of the head of the school. Keywords: Dhuha Prayer Habituation Method, Positive Character Of Children 5-6 Years Old